PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN - Tomi Prayogi; Apriatni Endang Prihatini; Widiartanto Widiartanto (Universitas Diponegoro, 2015)
PT. Masscom Graphy Semarang in carrying out operational activities would want a good performance of the employees, especially the production. But this is not easy because of the employee's performance is influenced by many factors. Such factors include leadership, work environment, and employees' organizational commitment factor.This study aims to determine the effect of leadership, work environment, and organizational commitment on employee performance of newspaper print production PT. Masscom Graphy Semarang. This type of research is explanatory research, with data collection through a questionnaire, literature study and interviews. Testing is done to the newspaper print production employees with a population of 42 people use the census method.The results showed that the leadership (X1), work environment (X2), and organizational commitment (X3) partially or simultaneously affect employee performance (Y) portion newspaper print production. Leadership has the greatest influence in affecting the performance of the employees this can be proven through multiple regression test results stating that the leadership has contributed 64.4%. While the organization's commitment to have the smallest influence in affecting the performance of employees with a contribution of 10.9%.